Biology of Glioblastoma Multiforme-Exploration of Mitotic Catastrophe as a Potential Treatment Modality - Vitovcova, Barbora; Skarkova, Veronika; Rudolf, Kamil; Rudolf, Emil (International journal of molecular sciences, 2020)
Glioblastoma multiforme (GBM) represents approximately 60% of all brain tumors in adults. This malignancy shows a high biological and genetic heterogeneity associated with exceptional aggressiveness, leading to a poor survival of patients. This review provides a summary of the basic biology of GBM cells with emphasis on cell cycle and cytoskeletal apparatus of these cells, in particular microtubules. Their involvement in the important oncosuppressive process called mitotic catastrophe will next be discussed along with select examples of microtubule-targeting agents, which are currently explored in this respect such as benzimidazole carbamate compounds. Select microtubule-targeting agents, in particular benzimidazole carbamates, induce G2/M cell cycle arrest and mitotic catastrophe in tumor cells including GBM, resulting in phenotypically variable cell fates such as mitotic death or mitotic slippage with subsequent cell demise or permanent arrest leading to senescence. Their effect is coupled with low toxicity in normal cells and not developed chemoresistance. Given the lack of efficient cytostatics or modern molecular target-specific compounds in the treatment of GBM, drugs inducing mitotic catastrophe might offer a new, efficient alternative to the existing clinical management of this at present incurable malignancy.
Keywords: glioblastom; M Phase Cell Cycle Checkpoints; Mitosis; kontrolní body M fáze buněčného cyklu; Glioblastoma; mitóza; nádory mozku; lidé; kontrolní body fáze G2 buněčného cyklu; Brain Neoplasms; G2 Phase Cell Cycle Checkpoints; Humans